2018
DOI: 10.1111/fcsr.12270
|View full text |Cite
|
Sign up to set email alerts
|

Financial Knowledge and Household Saving: Evidence from the Survey of Consumer Finances

Abstract: This study analyzed the relationship between financial knowledge and household saving behavior using the 2016 Survey of Consumer Finances (SCF) dataset. The results from a hierarchical model showed that both objective knowledge and perceived financial knowledge were positively related to the likelihood of being a saver. The explanatory power of the regression models increased significantly when financial knowledge variables were added. Furthermore, the results were robust across different measurements of house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
14
1
1
Order By: Relevance
“…The roles of financial literacy and possession of adequate cognitive ability have been widely studied in various financial behaviors and outcomes. This has been shown in studies of alternative financial services (Lusardi and Tufano, 2015; Robb et al ., 2015; Birkenmaier and Fu, 2018), stock market participation (Van Rooij et al ., 2011) and savings behavior (Lusardi, 2008; Kim and Yuh, 2018). With respect to retirement savings, Lusardi (2008) demonstrated a positive link between financial literacy and planning for retirement.…”
Section: Introductionmentioning
confidence: 99%
“…The roles of financial literacy and possession of adequate cognitive ability have been widely studied in various financial behaviors and outcomes. This has been shown in studies of alternative financial services (Lusardi and Tufano, 2015; Robb et al ., 2015; Birkenmaier and Fu, 2018), stock market participation (Van Rooij et al ., 2011) and savings behavior (Lusardi, 2008; Kim and Yuh, 2018). With respect to retirement savings, Lusardi (2008) demonstrated a positive link between financial literacy and planning for retirement.…”
Section: Introductionmentioning
confidence: 99%
“…Henager and Cude (2019) found that both objective knowledge and subjective knowledge were positively associated with having emergency funds across all age groups. Kim and Yuh (2018) documented the positive roles of both objective knowledge and subjective financial knowledge for the likelihood of spending less than income. Perceived financial capability is one’s self‐assessed money management ability.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Studies have found a positive association between financial education and financial outcomes (Kim & Yuh, 2018; Lusardi & Mitchell, 2007, 2008, 2014; Moore, 2003). Most of these studies have investigated the effect of cognitive knowledge with either short‐ or long‐term behavior.…”
Section: Literature and Conceptual Frameworkmentioning
confidence: 99%